A community-based survey on influenza and vaccination knowledge, perceptions and practices in Peru. Issue 5 (29th January 2020) - Reinders, Stefan; Romero, Candice; Carcamo, Cesar; Tinoco, Yeny; Valderrama, Maria; La Rosa, Sayda; Mallma, Patricia; Neyra, Joan; Soto, Giselle; Azziz-Baumgartner, Eduardo; Garcia, Patricia J.
Abstract: Background: Although Peru provides safe and effective influenza vaccines free-of-charge, coverage among vaccine target groups like pregnant women and older adults remains low. To improve risk communication messages and vaccine uptake, we explored knowledge, perceptions and practices about influenza illness and vaccination. Methods: A cross-sectional, community-based survey with a three-stage cluster sampling design was conducted in three cities in Peru. We included mothers of young children, pregnant women and persons ≥65 years. Participants completed a questionnaire about knowledge, perceptions and practices about influenza illness and vaccination against influenza during the past year. Generalized linear models were used to explore factors associated with vaccination in the past year. Results: 624/645 (97%) mothers, 54/55 (98%) pregnant women and 622/673 (92%) older adults approached provided informed consent and were surveyed. While most mothers, pregnant women and older adults (94%, 96% and 91%, respectively) perceived influenza as a potentially serious illness, few pregnant women (13%) and older adults (34%) self-identified themselves as a target group for influenza vaccination. Only 28% of mothers, 19% pregnant women, and 27% older adults were vaccinated against influenza during the previous year. Among the participants that did not get vaccinated against influenza in the previous year, "being afraid of vaccination and its effects" was the most commonly cited barrier. Knowledge of the recommendation for annual vaccination was significantly associated with vaccination status among pregnant women (p = 0.048) and older adults (p = 0.004). Conclusion: Despite a government subsidized vaccine program, vaccine utilization remained low among pregnant women and older adults, who seemed typically unaware of their status as high-risk groups targeted for vaccination. Those aware of the recommendations for annual vaccination were more likely to be vaccinated. Information campaigns addressing fears and highlighting populations at risk for severe influenza illness that are targeted for vaccination might increase vaccine coverage in Peru.